An efficient synthesis of versatile synthon 3-chlorooxindoles with NaCl/oxone. (22nd November 2018) - Lakshmi Reddy, Vanammoole; Prathima, Parvathaneni Sai; Rao, Vaidya Jayathirtha; Bikshapathi, Raktani
Abstract : The present work describes an expedient approach for the direct conversion of indole-3-carboxaldehyde to 3-chlorooxindoles. Abstract : The present work describes an expedient approach for the direct conversion of indole-3-carboxaldehyde to 3-chlorooxindoles using a simple sustainable synthetic method. From an environmental perspective, a combination of NaCl/oxone in a CH3 CN : H2 O (1 : 1) system was developed for direct oxidative chlorination of a wide array of indole derivatives. This chlorination strategy is more viable, remarkably cheaper and provides easy access to potential 3-chlorooxindoles. In addition, this environmentally benign method can also be applicable for constructing isatin derivatives in good yields.